Analisis Efisiensi Biaya Pengiriman dan Kualitas Freight Forwarder yang Mempengaruhi Kinerja Pengiriman Ekspor (Studi Kasus di PT. Sinar Sawit Sentosa) - Yoyo Sudaryo; Diki Wahyu Nugraha; Andre Suyaningprang; Gurawan Dayona Ismail; Wildan Guretno Prasetiyo (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
This study aims to analyze the influence of shipping cost efficiency and freight forwarder quality on export delivery performance at PT Sinar Sawit Sentosa, a palm oil exporting company facing challenges related to rising logistics costs and increasing demands for delivery timeliness. The research problem focuses on the extent to which shipping cost efficiency and the quality of freight forwarder services can improve export delivery performance in a measurable and sustainable manner. A quantitative approach was applied by collecting survey data from the company’s logistics managers and export managers to capture perceptions and experiences related to the research variables. Data analysis was conducted using structural equation modeling to examine the causal relationships among shipping cost efficiency, freight forwarder quality, and export delivery performance. The results indicate that shipping cost efficiency has a positive and significant effect on export delivery performance through reduced operational costs, improved logistics coordination, and smoother export processes. Freight forwarder quality is also proven to have a positive and significant effect through enhanced service reliability, documentation accuracy, and delivery timeliness. The conclusion confirms that the combination of cost efficiency and logistics service quality constitutes a strategic factor determining the success of corporate export delivery. The novelty of this study lies in integrating the measurement of cost efficiency and freight forwarder quality using a SEM approach applied to the Indonesian palm oil export industry, a context that has received limited empirical attention. This contribution provides empirical evidence for the development of export logistics management and strategic decision-making, enriches the academic logistics literature, and offers practical implications for improving national export competitiveness, formulating corporate policies, and managing long-term logistics partnerships based on measurable performance and efficiency orientation. The findings are expected to serve as a reference for future research and professional practice in agribusiness sectors oriented toward global markets with high logistics risks and intense competition that demand continuous, data-driven managerial innovation grounded in reliable and context-specific empirical evidence for the future of national industries.